REMOVAL OF COINS FROM OESOPHAGUS WITH FOLEY CATHETER UNDER KETAMINE EFFECT - Younas, Muhammad (Journal of Ayub Medical College Abbottabad, 2012)
Background: Foreign body ingestion continues to be a common problem that contributes significantly to high morbidity and mortality worldwide. Coins are the most common foreign body lodged in the oesophagus. This study was conducted to describe our experience of removal of coins from oesophagus with Foley catheter under ketamine effect. Methods: This was a retrospective study conducted at District Head Quarter Hospital, Buner. Foley’s catheter was used to remove the coins under ketamine effect. Results: Coins were successfully removed from 188 children without complications. Amongst these children 101 (53.72%) were male and 87 (46.28%) were female. The mean age of these children was 3.79 years. The coin was removed in first attempt in 154 (81.91%) cases. In 34 (18.08%) cases more than one attempts were required. The mean time for the removal of coin (i.e., initiation of catheter to removal of coin) was 55.30 seconds. The most commonly ingested coin was a one rupee coin (139, 73.93%), followed by two rupee coin (47, 25%), and 5 rupee coin (2, 1.06%). Conclusion: The coin impacted at the cricopharyngeus or upper oesophagus can be safely, easily, and quickly removed by Foley catheter under ketamine effect. Keywords: oesophagus, coin, foreign body, Foley catheter